Classification and regression tree analysis to predict calving ease in Sussex heifers using pelvic area dimensions and morphological trait - Bila, Lubabalo; Tyasi, Thobela Louis; Fourie, Pieter; Katikati, Aphiwe (Journal of Advanced Veterinary and Animal Research, 2020)
Objectives: The objective of this study was to assess the relationship between pelvic measurements, namely pelvic height (PH), pelvic area (PA), and pelvic width, and linear body measurement traits, such as hindquarters width, rump length (RL), hip height (HH), body weight (BW), shoulder height, chest depth (CD), body length, and also calve birth weight (CBW) under different calving ease scores, namely no assistance, gently pull, and hard pull. Material and Methods: A total of 51 first calf Sussex heifers at 24 months old, weighing approximately 440 ± 40.26 kg, were used for this study. Two-year-old bulls (n = 2), weighing approximately 800 kg, were used for mating the 51 heifers with a bull to cow ratio of 1:30 and 1:21. The fertility of bulls was assessed by a private veterinarian before the mating season. Calving ease was scored as follows: 1 = no assistance during parturition (normal), 2 = heifer assistance as gently pull, 3 = heifer assistance as hard pull, 4 = heifer cannot calf, 5 = heifer calved a dead calf, and 6 = heifer calf with the abnormal position. Results: Descriptive statistics indicated that PH (p < 0.01) and RL (p < 0.05) were positively remarkable and different among calving ease scores. Correlation results of the no assistance Sussex heifers group revealed that CBW was positively correlated (p < 0.05) with PH. Classification and regression tree CART results demonstrated that PH, BW, CD, and HH play an important role in predicting calving ease in Sussex heifers. Conclusion: The findings suggest that there is an association among PAs and biometric traits. The present study might help farmers select animals with higher PH, BW, CD, and HH during breeding to lower dystocia incidents during parturition. However, further studies need to be carried out in CART modeling to reduce dystocia in a larger sample size of Sussex heifers or other cattle breeds. J. Adv. Vet. Anim. Res., 8(1): 164-172, Mar 2021 http://doi.org/10.5455/javar.2021.h499